Integraler Grenzwertsatz für die konvergenz Gegen das stabile Grenzgesetz - Banys, J. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. И. Банис. Интегральная предельная теорема для сходимости к устойчивому законуJ. Banys. Integralinė teorema stabilaus ribinio dėsnio atveju